WATERFALL MODEL IMPLEMENTATION FOR DIGITAL HERITAGE: FINAL WEB QUALITY TESTING - Subiksa, Gde Brahupadhya; Adisimakrisna Peling, Ida Bagus; Agus Ariawan, Made Pasek (Universitas Teknokrat Indonesia, 2024)
Digital heritage is a concept or approach that uses digital technology to manage, preserve, and promote cultural heritage or historical objects in digital form. This allows for easier and wider access for the public to access information and explore cultural heritage without physically being present at the relevant location. For example, is the cultural heritage wayang in the regional treasures and Indonesia in general, wayang is an Indonesian identity that is recognized worldwide. Currently, knowledge and education about wayang and its character figures are very minimal, causing many future generations to not know the characters and epic stories of wayang. The solutions that can be taken from this problem is by utilizing the concept of digital heritage, which is a cultural heritage presented in digital form and can be accessed anytime through online media, so that information dissemination and education can reach more and wider audience. Information Technology Authentic Indonesian Ragawi Heritage Cultural Legacy with the Implementation of Digital Heritage Concept is a step to introduce the original Indonesian culture. The implementation of the digital heritage concept can be carried out through the Indonesian Wayang Kulit Heritage Information System. There are several menus and features in the system, namely: the homepage that shows the menu and original Indonesian wayang kulit, the information page that provides education to visitors, the wayang collection page that shows a number of popular puppet characters in Indonesia, the wayang character page that provides education and values held by each wayang character, and finally the purchasing page that aims to help wayang craftsmen. Overall, the testing shows that the system runs according to the expected features and functions. The final level of testing is also carried out with the aim of determining the quality of the system that has been built.